Experimental Investigation of Using Ethanol-Gasoline in Spark Ignition Engine - Nasir, Kadhim Fadhil (Al-Nahrain Journal for Engineering Sciences, 2018)
The consequence of mixing pure ethanol with gasoline on the pollution and performance of SI engine are investigated experimentally in the existent study. The SI engine that employed in the experiment is a single cylinder four stroke. Analysis is carried out for engine operation parameter, CO2, CO and unburned HC productions. The measurements are recorded for several engine speeds from 1500 – 3000 rpm with load and ethanol addition of (0E, 10E, 20E, 30E, 40E, 50E,). The results displayed increasing in brake power, and brake thermal efficiency while the brake specific fuel consumption decreases when the ethanol- gasoline blends fuel increases. Also it was found that CO, HC, and CO2 concentrations decrease when the ethanol- gasoline increases. The best results obtained in the study is for the blend of E-50.